56 Supraspinatus Tendinopathy: Assoications Of Subacromial Space And Scapular Muscle Strengths. (5th September 2014) - Leong, Hio-Teng; Tsui, Sammi; Gabriel, Yin-fat Ng; Fu, Siu Ngor
Abstract : Introduction: Shoulder impingement syndrome (SIS) is the mechanical entrapment of the supraspinatus tendon underneath the acromial arch of scapula. The narrowing of the subacromial space (SAS) was believed as one of the main contributing factors of SIS. Scapular muscles deficit is believed to cause abnormal scapular kinematics leading to the narrowing of subacromial space and SIS. This study aimed to compare the change of subacromial space during arm elevation between athletes of overhead sports with and without SIS; and its association with scapular muscle strengths. Methods: Seventy-two athletes participating in volleyball and baseball (mean age=22.3 ± 3.6) were tested and among them, 39 had SIS. An Aixplorer ® ultrasound machine (SuperSonic Imagine, Aix-en-Provence, France) was used to measure the subacromial space (SAS) during arm at rest, at 30° and 60° of shoulder abduction. Isometric strengths of upper trapezius (UT), middle trapezius (MT), lower trapezius (LT), and serratus anterior (SA) were measured by microFET2 Digital Handheld Dynamometry (Cools, 2010). SAS was defined as the tangential distance between the humeral head and the infero-lateral edge of acromion (Figure 1 ) (Desmeules, 2004). The change of SAS during arm abduction from 0° to 30° (SAS0°-30° ), 30° to 60° (SAS30°-60° ), and 0° to 60° (SAS0°-60° ) were calculated. Results: Our findings revealed significant reduction of SAS during arm abduction from 0° to 60° (p = 0.000) (Figure 2 ). The changes in SAS0°-30° was greater in athletes with SIS (0.35 ± 1.12 mm) than healthy athletes (-0.06 ± 1.41 mm) (p = 0.033) (Table 1 ). Besides, athletes with SIS had significantly decreased scapular strengths (UT, MT, LT and SA) than their healthy counterparts (all p < 0.05). In healthy overhead athletes, correlation analysis showed weaker middle trapezius and lower trapezius were associated with greater reduction of SAS0°-30° (r=-0.445, p = 0.016 and -0.423, p = 0.022; respectively). Such relationship could not be detected in athletes with SIS. Discussion: Our findings demonstrated greater reduction in the subacromial space in early abduction in volleyball and baseball players with SIS than healthy control. The middle and lower trapezius muscles are the scapular muscles associated with the change in the subacromial space in the healthy players. References: Cools et al . Br J Sports Med. 2010;44(9):678–684 Desmeules et al . Clin J Sport Med. 2004;14(4):197–205